Chemical and pharmacological characterisation of some traditional remedied used by bomoh's in the management of drug addiction - Yunus, Amiru'd-Din (1980)
In the present investigations, the samples obtained from Bomohs were examined for their properties which were claimed that can be used in the management of narcotic addiction. These were studied from various aspects of the narcotic addiction in the mice. All together six samples were studies and were labelled as Sample I, Sample n, Sample III, Sample IV, Sample V and Sample VI. Morphine tolarence in mice were induced by a single dose as described by Jacob J.J. et. al., (1972, 1974). The precipitated withdrawal syndromes were induced using nalorpbine, the narcotic antagoniat.